Independent Supported Housing for Non-homeless People With Serious Mental Illness: A Pragmatic Randomized Controlled Trial - Mötteli, Sonja; Adamus, Christine; Deb, Tim; Fröbel, Rahel; Siemerkus, Jakob; Richter, Dirk; Jäger, Matthias (Frontiers in Psychiatry, 2022)
Background Independent supported housing (ISH) – services to support independent housing are recommended by current guidelines. However, there is little evidence of ISH models for non-homeless people with severe mental illness (SMI). The aim of this study was to examine the effectiveness of ISH by comparing the clinical outcomes of a newly implemented ISH service with regular housing and support services. Methods A total of 58 adults with a broad spectrum of mental disorders experiencing housing problems were randomly assigned to either the intervention group (IG) with the possibility to use the ISH service in Zurich providing targeted, individual and flexible support for housing problems or to the control group (CG) with regular housing and support services currently available (trial registration at ClinicalTrials.gov: NCT03815604). Results After 12 months, almost all participants of the IG were able to live independently and need for inpatient treatment could be significantly reduced. Service utilization varied between 2 and 79 hours. In the CG, 70% of the participants wanted to join a waiting list for the ISH service. The results indicated that IHS was comparable to regular housing and support services in terms of social inclusion and other social and clinical outcomes such as quality of life, capabilities, needs, mental state and functioning (p’s > 0.05). The costs of service utilization were on average 115 Swiss Francs (about 124 USD) per participant per month. Conclusions ISH is an effective service in housing rehabilitation in terms of social and clinical outcomes and costs. ISH is strongly preferred by service users. In line with the UN Convention on the Rights of Persons with Disabilities, access to ISH services for non-homeless people with SMI should be improved.